Features arabisms and persisms in Kazakh and Turkish languages - Nazarova, A. Zh.; Saduova, Sh. M. (Journal of Oriental Studies, 2016)
In this article arabisms and persisms in Kazakh and Turkish languages are considered. Lexical and grammatical changes, arab-persian phonetics introduced in the language are considered too.